2018
DOI: 10.2147/ijn.s171361
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis activated by oncogenic Dbl enables specific targeted delivery of Tat/pDNA nano-complexes into ovarian cancer cells

Abstract: BackgroundSuccessful implementation of gene therapy heavily relies on efficiently delivering genetic materials and specific targeting into cells. Oncogene-driven endocytosis stimulates nutrient uptake and also develops an endocytosis-mediated defense against therapeutic agents. Cell-penetrating peptides, typically HIV-Tat, are well known for efficient delivery of nucleic acid drugs but lack targeting specificity. Various passive targeting strategies were pursued to enhance the tumor targeting efficiency; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The pLV-RNAi system (BIOSETTIA, SORT-B19) was utilized to produce Arf6-KD (knocked-down) stable cell lines. Three independent Arf6-targeting shRNA (A1: AAAAGGAAGGTGCTATCCAAAATTTGGATCCAAATTTTGGATAGCACCTTCC, A2: AAAACAACAATCCTGTACAAGTTGATTGGATCCAATCAACTTGTACAGGATTGTTG, and A3: AAAAGCTCACATGGTTAACCTCTAATTGGATCCAATTAGAGGTTAACCATGTGAGC) were generated as previously described [29]. Arf6(wt) and Arf6(Q67L) plasmids were transfected in liver cancer cells for gene over-expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pLV-RNAi system (BIOSETTIA, SORT-B19) was utilized to produce Arf6-KD (knocked-down) stable cell lines. Three independent Arf6-targeting shRNA (A1: AAAAGGAAGGTGCTATCCAAAATTTGGATCCAAATTTTGGATAGCACCTTCC, A2: AAAACAACAATCCTGTACAAGTTGATTGGATCCAATCAACTTGTACAGGATTGTTG, and A3: AAAAGCTCACATGGTTAACCTCTAATTGGATCCAATTAGAGGTTAACCATGTGAGC) were generated as previously described [29]. Arf6(wt) and Arf6(Q67L) plasmids were transfected in liver cancer cells for gene over-expression.…”
Section: Methodsmentioning
confidence: 99%
“…After subjecting the collected pellets to SDS-PAGE, the GTP-bound Rab5 and Rab22 in samples were determined by Western blot. The Rac1-GTP level was assessed using GST-PAK-CRIB immobilized beads as previously described [29, 32, 33].…”
Section: Methodsmentioning
confidence: 99%
“…According to bioinformatics analysis, RAC1 was enriched in various BPs, such as ‘regulation of receptor-mediated endocytosis’, ‘cell morphogenesis’, ‘cellular component morphogenesis’ and ‘epithelial cell differentiation’. These BPs play important roles in the growth, migration and differentiation of tumor cells, thereby contributing to the occurrence and development of cancer (7780). Additionally, the data in the present study revealed that the upregulation of RAC1 was associated with poorer OS in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 uptake and binding were measured as previously described 4851 . Incubation conditions for the H18Ab complex were optimized (H18Ab, 1:500, anti-mouse AF488, 1:1000, 15 min) in HCC cells.…”
Section: Methodsmentioning
confidence: 99%